Management of Infrastructure in Vocational High Schools - Ante, Lady D.; Sumual, Tinneke EM; Monigir, Norma N (Abdurrauf Journal of Education and Islamic Studies, 2025)
This study aims to explore the management of educational facilities and infrastructure at Christian Private Vocational High School, Christian Education Foundation in Manado, Evangelical Christian Church in Minahasa, with a specific focus on the Computer and Network Engineering department. The research is grounded in the reality that many key learning facilities—such as computer laboratories and internet networks—have not been managed effectively. However, the availability of appropriate resources is essential to support technology-based learning, especially in vocational education settings. A qualitative approach was used, with data collected through in-depth interviews, direct observation, and document analysis. The findings reveal that although planning for facility procurement has taken place, there are still significant challenges in the areas of organization, implementation, and supervision. The lack of a structured management system and limited technical personnel have led to poorly maintained facilities. Moreover, the involvement of teachers and students in reporting issues and maintaining equipment remains minimal. This study highlights the importance of applying the POAC management principles (Planning, Organizing, Actuating, and Controlling) in the administration of school infrastructure. The results are expected to serve as strategic input for the school, helping to create a more supportive and efficient learning environment that prepares students to compete in a technology-driven workforce.